The mediation effect of intention in the pro-environmental workplace (PEW) behavior of Malaysian public employees - Mohamad Fazli Sabri; Norjumaaton Fazhani Razak; Rusitha Wijekoon (Management Science Letters, 2019)
During the past few years, many studies associated with sustainability of the organizations have primarily analyzed the financial and performance related implications of sustainability of an organization, and perception of these practices by neglecting the role of the employees who might play a vital role through taking part in pro-environmental behavior in the workstation. Thus, this study focuses on the individual’s pro-environmental workplace (PEW) intention to determine its mediating effect between the factors in the Theory of Planned Behavior (TPB) and the PEW behavior context among public workers in Malaysia. Random sampling on a list of ministries situated in Federal Territory of Putrajaya was used in the first stage followed by systematic sampling based on officer’s list of the directory in those ministries. Cleaned data resulted in 460 questionnaires gathered on demographic characteristics, PEW intention, attitude towards environmental practice in the workplace, subjective norms, perceived environmental workplace control, and PEW behavior of public sector context in Malaysia. The results reveal significant influences of PEW subjective norms, and perceived PEW control on the PEW behavior. While a series of regression analyses show that the PEW intention mediated only the two relationships between PEW subjective norms, and perceived PEW control on PEW behavior.